COSMOS2020: Identification of High-z Protocluster Candidates in COSMOS - Malte Brinch; Thomas R. Greve; John R. Weaver; Gabriel Brammer; Olivier Ilbert; Marko Shuntov; Shuowen Jin; Daizhong Liu; Clara Giménez-Arteaga; Caitlin M. Casey; Iary Davidson; Seiji Fujimoto; et al. (The Astrophysical Journal, 2023)
We conduct a systematic search for protocluster candidates at z ≥ 6 in the Cosmic Evolution Survey (COSMOS) field using the recently released COSMOS2020 source catalog. We select galaxies using a number of selection criteria to obtain a sample of galaxies that have a high probability of being inside a given redshift bin. We then apply overdensity analysis to the bins using two density estimators, a Weighted Adaptive Kernel estimator and a Weighted Voronoi Tessellation estimator. We have found 15 significant (>4 σ ) candidate galaxy overdensities across the redshift range 6 ≤ z ≤ 7.7. The majority of the galaxies appear to be on the galaxy main sequence at their respective epochs. We use multiple stellar-mass-to-halo-mass conversion methods to obtain a range of dark matter halo mass estimates for the overdensities in the range of ∼10 ^11 –10 ^13 M _⊙ , at the respective redshifts of the overdensities. The number and the masses of the halos associated with our protocluster candidates are consistent with what is expected from the area of a COSMOS-like survey in a standard Λ cold dark matter cosmology. Through comparison with simulation, we expect that all of the overdensities at z ≃ 6 will evolve into Virgo-/Coma-like clusters at present (i.e., with masses ∼10 ^14 –10 ^15 M _⊙ ). Compared to other overdensities identified at z ≥ 6 via narrowband selection techniques, the overdensities presented appear to have ∼10× higher stellar masses and star formation rates (SFRs). We compare the evolution in the total SFR and stellar mass content of the protocluster candidates across the redshift range 6 ≤ z ≤ 7.7 and find agreement with the total average SFR from simulations.